BMSC-Exosomes Carry Mutant HIF-1α for Improving Angiogenesis and Osteogenesis in Critical-Sized Calvarial Defects - Ying, Chenting; Wang, Rui; Wang, Zhenlin; Tao, Jie; Yin, Wenjing; Zhang, Jieyuan; Yi, Chengqing; Qi, Xin; Han, Dan (Frontiers in Bioengineering and Biotechnology, 2020)
Repair and reconstruction of critical-sized bone defects has always been a difficult task in orthopedics. Hypoxia inducible factor-1α (HIF-1α) plays an important role in bone defect repair, it has the dual function of promoting osteogenesis and vascular regeneration, but it is quickly degraded by the body under normoxic conditions. Previously we prepared mutant HIF-1α, which has been shown to efficiently maintain cellular expression under normoxic conditions. In this study, we evaluated for the first time the role of exosomes of rat bone marrow mesenchymal stem cell carry mutant HIF-1α (BMSC-Exos-HIF1α) in repairing critical-sized bone defects. Evaluation of the effects of BMSC-Exos-HIF1α on bone marrow mesenchymal stem cells (BMSCs) proliferation and osteogenic differentiation by cell proliferation assay, alkaline phosphatase activity assay, alizarin red staining, real-time quantitative polymerase chain reaction. BMSC-Exos-HIF1α was loaded onto the β-TCP stent implanted in the bone defect area using a rat cranial critical-sized bone defect model, and new bone formation and neovascularization were detected in vivo by micro-CT, fluorescence labeling analysis, Microfil perfusion, histology and immunohistochemical analysis. In vitro results showed that BMSC-Exos-HIF1α stimulated the proliferation of BMSCs and up-regulated the expression level of bone-related genes, which was superior to bone marrow MSC exosomes (BMSC-Exos). In vivo results showed that BMSC-Exos-HIF1α combined with β-TCP scaffold promoted new bone regeneration and neovascularization in the bone defect area, and the effect was better than that of BMSC-Exos combined with β-TCP scaffold. In this study, the results showed that BMSC-Exos-HIF1α stimulated the proliferation and osteogenic differentiation of BMSCs and that BMSC-Exos-HIF1α combined with β-TCP scaffolds could repair critical-sized bone defects by promoting new bone regeneration and neovascularization.